Static security assessment on power system using artificial neural network [compact disc] - 619461 Mohd. Fadli Rahmat (Skudai : Universiti Teknologi Malaysia, 2005)
Thesis (Sarjana Kejuruteraan (Elektrik - Kuasa)) - Universiti Teknologi Malaysia, 2005